Genetic diversity, tissue-specific expression, and functional analysis of the ATP7A gene in sheep - Li, Hao; Du, Xiaolong; Li, Xinyue; Feng, Pingjie; Chu, Mingxing; Jin, Yi; Pan, Zhangyuan (Frontiers in Genetics, 2023)
In humans, variation of the ATP7A gene may cause cranial exostosis, which is similar to "human horn", but the function of the ATP7A gene in sheep is still unknown. Tissue expression patterns and potential functional loci analysis of the ATP7A gene could help understand its function in sheep horn. In this study, we first identified tissue, sex, breed, and species-specific expression of the ATP7A gene in sheep based on the RNA-sequencing (RNA-seq) data. Second, the potential functional sites of the ATP7A gene were analyzed by using the whole genome sequencing (WGS) data of 99 sheep from 10 breeds. Last, the allele-specific expression of the ATP7A gene was explored. Our result showed the ATP7A gene has significantly higher expression in the big horn than in the small horn, and the ATP7A gene has high expression in the horn and skin, suggesting that this gene may be related to the horn. The PCA results show that the region around the ATP7A can distinguish horned and hornless groups to some extent, further indicating that the ATP7A may be related to horns. When compared with other species, we find 7 ruminate specific amino acid sites of the ATP7A protein, which can be important to the ruminate horn. By analyzing WGS, we found 6 SNP sites with significant differences in frequency in horned and hornless populations, and most of these variants are present in the intron. But we still find some potential functional sites, including three missenses, three synonymous mutations, and four Indels. Finally, by combining the RNA-seq and WGS functional loci results, we find three mutations that showed allele-specific expression between big and small horns. This study shows that the ATP7A gene in sheep may be related to horn size, and several potential functional sites we identified here can be useful molecular markers for sheep horn breeding.